THE INFLUENCE OF CONSUMER BELIEFS AND EMOTIONALITY ON CONSUMER SATISFACTION IN THE SENTUL SCOUTING EARTH UNIT, BOGOR - Silaningsih, Endang; Rahayu, Nuratih Dewi; Ismartaya, Ismartaya (Universitas Nusa Cendana, 2025)
The aim of this research is to determine consumer loyalty in the Bumi Kepanduan Unit Sentul Bogor which is influenced by consumer trust, emotions through consumer satisfaction, and 100 people were sampled. Meanwhile, the analytical method used is the quantitative descriptive method and path analysis. The results of the research show that consumer trust has a positive and significant effect on consumer satisfaction; emotionality has a positive and significant effect on consumer satisfaction; consumer trust has a direct positive and significant effect on consumer loyalty; emotional has a direct positive and significant effect on consumer loyalty; consumer satisfaction has a direct positive and significant effect on consumer loyalty; consumer trust has an indirect and positive effect on consumer loyalty through consumer satisfaction at the Sentu Bogor Scouting Unit; and emotion has an indirect and positive effect on consumer loyalty through consumer satisfaction at the Sentu Bogor Scouting Earth Unit. Keywords: Consumer Confidence; Emotional; Consumer Loyalty ; Consumer Satisfaction